Hubungan Indeks Massa Tubuh dan Kadar Antibodi IgG Pasca Vaksinasi COVID-19 - Andry Ganesha Rombe; I Ketut Suardamana (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Body Mass Index (BMI) is a standard measure to assess nutritional status and potential health risks. During the COVID-19 pandemic, BMI has been associated with varying disease severity and immune responses. As vaccines remain essential to pandemic control, post-vaccination IgG levels have become a key indicator of protection. However, the impact of BMI on IgG responses remains unclear, with studies showing mixed results. This study aims to evaluate the relationship between BMI and IgG antibody levels after COVID-19 vaccination. A cross-sectional study was conducted involving 76 respondents. Data collected included BMI (based on WHO classification), weight, height, history of COVID-19 infection, vaccine type, and number of doses. IgG levels were measured using immunoassay techniques. Correlations were analyzed using Spearman’s rho and Pearson tests. No significant correlation were found between BMI and IgG levels (r = -0.159; p = 0.242). Weight (r = -0.029; p = 0.833) and height (r = -0.064; p = 0.638) also showed no association with IgG levels. A weak positive correlation was observed between prior COVID-19 infection and IgG level (r = 0.231; p = 0.087), though not statistically significant. BMI, body weight, and height did not significantly influence IgG antibody levels following COVID-19 vaccination. Prior infection may have a slight effect, but rises requirements for further studies involving larger populations to clarify this potential relationship.